2003
DOI: 10.1089/152308603770380025
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Reactive Oxygen Species-Induced p38 MAP Kinase Activation and Barrier Dysfunction in Lung Microvascular Endothelial Cells

Abstract: Reactive oxygen species (ROS)-mediated compromise of endothelial barrier integrity has been implicated in a number of pulmonary disorders, including adult respiratory distress syndrome, pulmonary edema, and vasculitis. The mechanisms by which ROS increase endothelial permeability are unclear. We hypothesized that ROS-induced changes in cellular redox status (thiols) may contribute to endothelial barrier dysfunction. To test this hypothesis, we used N-acetylcysteine (NAC) and diamide to modulate intracellular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 38 publications
7
95
1
2
Order By: Relevance
“…Nevertheless, our data do not rule out ROS- independent mechanisms by which sustained adenosine activates p38 and JNK in mitochondria, leading to barrier dysfunction. We and others have previously shown that p38 mediates EC barrier dysfunction and lung edema (34,57). The p38 downstream targetHSP27 modulates actin filament dynamics via its phosphorylation, thus affecting endothelial permeability.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, our data do not rule out ROS- independent mechanisms by which sustained adenosine activates p38 and JNK in mitochondria, leading to barrier dysfunction. We and others have previously shown that p38 mediates EC barrier dysfunction and lung edema (34,57). The p38 downstream targetHSP27 modulates actin filament dynamics via its phosphorylation, thus affecting endothelial permeability.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, oxidative stress is known to induce signaling cascades and subsequent cytoskeletal remodeling in a number of neural and non-neural cell systems (Bundy et al, 2005;Carvalho et al, 2004;Choi et al, 2004;Huot et al, 1998;Kevil et al, 2001;Kurata, 2000;Usatyuk and Natarajan, 2004;Usatyuk et al, 2003). In dopaminergic neurons, phosphorylation of p38 MAPK by oxidative stress is linked to activation of caspases and apoptotic pathways (Choi et al, 2004) and p38 MAPK mediates the formation of actin stress fibers induced by β-amyloid peptide (Song et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been reported to stimulate signaling pathways including the mitogen-activated protein kinases (MAPK) (Choi et al, 2004;Huot et al, 1998;Kurata, 2000;Rosenberger et al, 2001;Song et al, 2002;Usatyuk et al, 2003). In this study, western blot analysis was used to demonstrate that H 2 O 2 triggers the p38 MAPK pathway in astrocytes and phosphorylation of p38 MAPK increased with increasing dose of H 2 O 2 ( Fig.…”
Section: H 2 O 2 Stimulates P38 Mapk In Astrocytesmentioning
confidence: 94%
“…In rat AT2 cells and immortalised human airway epithelial cells (A549), cyclic mechanical strain increases ROS production in a dose-dependent manner once a critical threshold is reached [100], and the same has been seen in bovine pulmonary arteries [101]. A number of targets for ROS-induced permeability changes have been suggested, and include vascular endothelial growth factor (VEGF), endothelial growth factor and subsets of the mitogen-activated protein kinase cascades [102], yet the actual effector mechanisms downstream remain elusive.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%